An Assessment Of The Use, Benefits And Challenges Of The ‘Cash–Lite’ Policy, For Construction Projects In Anambra State, Nigeria - Fidelis Okechukwu Ezeokoli; Stanley Chukwudi Ugochukwu; Nathan Ndubuisi Agu; Samuel Chukwujekwu Akabogu (European Scientific Journal, ESJ, 2016)
The introduction of the ‘Cash-Lite; a cashless policy, by the Central Bank of Nigeria in 2011 has changed the modus operandi of the construction industry. This is because the industry is one of the few industries that deal mostly with cash. Hence, this study is aimed at examining the development and implementation of the Nigerian ‘Cash-Lite’ policy, with a view to ascertain its effects on construction practice. The study examined 300 construction stakeholders using questionnaires. Data obtained from these sources was analysed using charts, table of frequency, mean scores and Ztest. However, the data analysis was aided by a computer database software packages - SPSS Statistic. The study observed that the integration of cashless policy into construction work will boost productivity/construction output via reducing the rate of visit to banks, reducing theft/corruption, reducing project time and encourage prompt settlement of transaction. In addition to this, the study observed that the structure of the industry encourages the integration of this policy to construction but security (cyber theft), lack of knowledge, cost of installation and operation, reliability of the service and supporting services and low public acceptance are the major challenges affecting its adoption in construction. Finally, the study recommends that construction workers and other construction stakeholders should be properly sensitized on the use of cashless tools.